Surgical treatment of meningiomas invading the superior sagittal sinus - Kvasha, Michail S.; Spiridonov, Anatolii V. (Ukrainian Neurosurgical Journal, 2024)
Objective: To investigate the impact of the degree of invasion of the superior sagittal sinus by meningiomas on the radicality of removal and to assess the risks of complications during surgical intervention for superior sagittal sinus meningiomas. Materials and Methods: The study included 82 patients who underwent surgery at the Romodanov Neurosurgery Institute over the past 10 years (from 2013 to 2023). The cohort comprised 53 women and 29 men, with an average age of 43.4±1.7 years. Inclusion criteria are: a histologically confirmed diagnosis of meningioma and evidence of superior sagittal sinus invasion based on neuroimaging (MRI with intravenous contrast enhancement, MSCT angiography). Results: A total of 84 surgical procedures were performed on 82 patients. Among these, 71 were primary cases (84.5%), and 13 were secondary cases (15.5%). In 7 out of 13 secondary surgeries, superior sagittal sinus invasion was first detected through neuroimaging and confirmed intraoperatively. Postoperative hemiparesis of varying degrees was observed in 41 patients (50%), with 10 cases showing an increase in neurological deficits due to surgical intervention. Motor deficits completely regressed within 3-6 months post-surgery in 28 out of 41 patients. Tumor recurrence was identified in 4 patients (4.9%) within 2.5-6 years after the primary surgery. Among these, 3 were morphologically confirmed as "anaplastic meningioma Grade III," and 1 as "atypical meningioma Grade II". Conclusions: Meningiomas originating from the arachnoid membrane constitute a significant proportion of primary intracranial tumors, with varying degrees of venous sinus invasion. Surgical planning for meningiomas invading the superior sagittal sinus should consider the radiological classification of invasion degrees, which aids in determining the treatment strategy. MRI with intravenous contrast and MSCT angiography are crucial for identifying collateral blood flow and assessing the degree of venous sinus invasion before surgical intervention.